Governance arrangements for specialized assistance in health regions in Brazil - Luciana Dias de Lima; João Henrique Gurtler Scatena; Mariana Vercesi Albuquerque; Ricardo Antunes Dantas de Oliveira; Nereide Lucia Martinelli; Adelyne Maria Mendes Pereira
Abstract Objectives: to analyze the regional governance arrangements of specialized assistance in the Public Health System (SUS). Methods: Case studies were carried out which included seven health regions in the Brazilian territory, involving the secondary data systematization and 128 interviews with SUS leaders (2015 to 2016). The analysis was done in a comparative perspective, considering: public and private participation; assistance concentration; power relations and regional conflicts. Results: the public provision service and expenditure were high in the Medium Complexity and in the private, High Complexity. The main responsibility for the public provision service was in the cities so, that the specialized assistance was strongly concentrated in the pole cities. The level of influence from the providers in health decisions was high, and the offer considered to be insufficient and inadequate in relation to services and medical professionals. Conflicts were evident in the intergovernmental and public-private relations. Conclusions: the diversity of agents and arrangements - multilevel, hybrid and polarized - characterizes governance regionalization in SUS, which is conditioned by the scarcity and the inequality context in the distribution of services.